2022
DOI: 10.1073/pnas.2121520119
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation and homeostasis of effector Treg cells are regulated by inositol polyphosphates modulating Ca2+influx

Abstract: Activated Foxp3 + regulatory T (Treg) cells differentiate into effector Treg (eTreg) cells to maintain peripheral immune homeostasis and tolerance. T cell receptor (TCR)–mediated induction and regulation of store-operated Ca 2+ entry (SOCE) is essential for eTreg cell differentiation and function. However, SOCE regulation in Treg cells remains unclear. Here, we show that inositol polyphosphate multikinase (IPMK), which generates inositol tetrakisphosphate and ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Recently, conditional deletion of IPMK in Treg cells revealed its essential role for the regulatory function and differentiation of Treg cells into effector Treg cells. Mechanistically, IPMK’s catalytic activity as an IP kinase was found to promote InsP 3 -mediated store-operated Ca 2+ entry (SOCE) via IP 4 [Ins(1,3,4,5)P 4 ] production in Treg cells (Min, Kim et al 2022). In contrast, our results in the present study revealed that Th cells depend on the lipid PI3-kinase function of IPMK to regulate activation of mTOR signaling, which directly modulates STAT3 activation and governs Th1 and Th17 cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, conditional deletion of IPMK in Treg cells revealed its essential role for the regulatory function and differentiation of Treg cells into effector Treg cells. Mechanistically, IPMK’s catalytic activity as an IP kinase was found to promote InsP 3 -mediated store-operated Ca 2+ entry (SOCE) via IP 4 [Ins(1,3,4,5)P 4 ] production in Treg cells (Min, Kim et al 2022). In contrast, our results in the present study revealed that Th cells depend on the lipid PI3-kinase function of IPMK to regulate activation of mTOR signaling, which directly modulates STAT3 activation and governs Th1 and Th17 cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…As a multifunctional signaling molecule, calcium is required for a number of biological processes, including cell proliferation, differentiation, and apoptosis [ [35] , [36] , [37] ]. Further, lipid accumulation in adipocytes is strongly influenced by intracellular Ca 2+ homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium signaling has been reported to regulate cell differentiation positively or negatively in a variety of cell types. For example, intracellular calcium is essential for Treg cells differentiation into effector population and keratinocyte differentiation [ 35 , 36 ], but limits the differentiation of B cells and adipocytes [ 37 , 38 ]. As for myeloid progenitor cells, calcium and calcineurin signaling have been shown to inhibit cell cycle progression of GMPs to regulate myeloid cell differentiation [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Next, we wondered what intracellular mechanisms mediated these changes. Considering the significant enriched calcium-mediated pathways in myeloid cells after GSDMD knockout, and the important role of calcium in cell differentiation [ 35 38 ], we thus assumed GSDMD deficiency-induced differentiation was calcium-related. Measuring calcium influx by flow cytometry, we observed that GSDMD deficiency attenuated calcium influx in ATRA-treated NB4 (Fig.…”
Section: Gsdmd-deficient Myeloid Cells From Lupus Spleen Exhibit Imma...mentioning
confidence: 99%